Determinan Adopsi Penggunaan Teknologi Informasi pada Badan Usaha Milik Desa - Arista, Denty; Nugrahaningsih, Putri; Rahmawati, Labbaika Dwi Ayu; Saputra, Zaim Arif Eko; Tiaramurti, Galuh (Jurnal Akuntansi dan Bisnis, 2024)
This study aims to measure the level of each behavioural factor on the acceptance and use of information systems of entities without public accountability in the Madiun Regency. The Unified Theory of Acceptance and Use of Technology (UTAUT) model measures the relationship between behaviour and technology. Factors influencing behaviour, such as performance expectations, behavioural intentions, and trust, have a close relationship in adopting information systems in a BUMDes organization in Madiun Regency to develop an information system platform that becomes a hub between micro business entities and buyers. However, the acceptance of micro business entities towards the information system is still less than optimal, which is based on dissatisfaction with the internet infrastructure and facility conditions, which harms the acceptance of technology adoption. This study used a quantitative approach using regression analysis. The entire population of micro entities, totalling 76, became respondents in this study. The results indicate that behavioural factors in the form of technological readiness, organizational readiness, and the external environment positively affect the use of information technology.